2020
DOI: 10.1093/jnen/nlz129
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Stress Response and Phosphorylated Eukaryotic Initiation Factor 2α in Neurodegeneration

Abstract: The proposed molecular mechanisms underlying neurodegenerative pathogenesis are varied, precluding the development of effective therapies for these increasingly prevalent disorders. One of the most consistent observations across neurodegenerative diseases is the phosphorylation of eukaryotic initiation factor 2α (eIF2α). eIF2α is a translation initiation factor, involved in cap-dependent protein translation, which when phosphorylated causes global translation attenuation. eIF2α phosphorylation is mediated by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 231 publications
2
74
0
Order By: Relevance
“…CReP is constitutively expressed and promotes peIF2α dephosphorylation in physiological conditions [ 6 ], whereas GADD34 reduces the ISR during ER stress in an ATF4-dependent manner following a negative feedback loop [ 7 , 8 ]. Interestingly, enhancing the ISR through pharmacological inhibition of GADD34-mediated peIF2α dephosphorylation provides neuroprotection in several models of neurodegeneration [ 9 ]. Salubrinal, pharmacological inhibitor of both CReP and GADD34 [ 10 ], provides neuroprotection [ 11 ] but it may have detrimental effects due to persistent translational inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…CReP is constitutively expressed and promotes peIF2α dephosphorylation in physiological conditions [ 6 ], whereas GADD34 reduces the ISR during ER stress in an ATF4-dependent manner following a negative feedback loop [ 7 , 8 ]. Interestingly, enhancing the ISR through pharmacological inhibition of GADD34-mediated peIF2α dephosphorylation provides neuroprotection in several models of neurodegeneration [ 9 ]. Salubrinal, pharmacological inhibitor of both CReP and GADD34 [ 10 ], provides neuroprotection [ 11 ] but it may have detrimental effects due to persistent translational inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is perhaps unsurprising that modulation of the PERK-eIF2α signaling has emerged as a promising therapeutic target for neurodegenerative disease. Much of the research focus regarding either pharmacological or genetic inhibition of PERK signaling to reduce p-eIF2α levels has been placed on models of pathology, suggesting a neuroprotective effect of restored eIF2α-dependent translation in mice 18, 5254 . However, there is other evidence from studies of preclinical models of neurodegenerative disorders that depict a complex scenario where, depending on the disease context, modulation of PERK-branch mediated translational control may result in contrasting and even opposite effects 19, 20, 55 .…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known that, in response to stress conditions, such as ER stress from misfolded proteins, oxidative stress or viral infections, the ISR pathway is activated, leading to the phosphorylation of eIF2α and causing global cap-dependent translation attenuation but upregulation of the translation of certain mRNAs in an unconventional manner [61][62][63][64]. Recent mechanistic studies on RAN translation clearly indicate that cellular stress is another trigger for this non-canonical mode of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In response to diverse stress stimuli such as hypoxia, viral infections or the presence of misfolded proteins, eukaryotic cells activate a cytoprotective signaling pathway termed the integrated stress response (ISR) to restore cellular homeostasis. The core event of ISR is phosphorylation of the α subunit of eIF2, which leads to global protein synthesis attenuation accompanied by the induction of alternative mechanisms of translation initiation of selected mRNAs [61][62][63][64]. Recently, it has been reported that RAN translation at CGG and GGGGCC repeats is enhanced by ISR activation [26,27,29,36].…”
Section: Cellular Stress Enhances Sca3 Ran Translation Of the Cag Repmentioning
confidence: 99%